(untitled) (Dhaka University Journal of Biological Sciences, 2014)
Effects of five different concentrations of sodium chloride (5 to 25%) treated fish flesh was tested on oviposition, growth and developmental parameters of blowfly, Lucilia cuprina (Wiedemann). The salt worked as an oviposition deterrent in the female flies. The highest amount of eggs (0.247 ± 0.0464 g) was oviposited on lowest salt concentration (5%) and the minimum amount (0.0003 ± 0.0004 g) of eggs was laid on the highest salt concentration (25%). The eggs laid on 20 and 25% salt treated fishes were not hatched. The larval periods were significantly affected by 10 and 15% salt treated fish while the pupal periods were prolonged at 15% of salt treated fish (p < 0.05). Average larval and pupal durations in control were 4.543 ± 0.18 and 4.833 ± 0.753 days, respectively, whereas at 15% salt average larval and pupal durations were 5.937 ± 0.133 and 5.5 ± 0.548 days, respectively. The average weight of the larvae and pupae were also reduced with the high concentrations of salt. Pupation rate also significantly reduced at higher concentrations of salt. These results suggest that application of 15% salt in raw fish can effectively protect sun?drying fish from blowfly infestation. DOI: http://dx.doi.org/10.3329/dujbs.v23i1.19825 Dhaka Univ. J. Biol. Sci. 23(1): 47-51, 2014